Training Female Bodies for New India: Women's Physical Education between Global Trends and Local Politics in Colonial South Asia, c. 1900–1939. Issue 11 (2nd September 2022) - Valdameri, Elena
Abstract: This paper explores the emergence of modern female physical education in late colonial India in the period between the beginning of the twentieth century and the late 1930s. Focusing mostly on physical training schemes directed at middle-class, upper-caste Hindu girls and women, the study provides detail about the role played by a variety of Indian and non-Indian historical actors that were committed to the spread of female physical fitness. It demonstrates that, despite different ideological tendencies, political agendas and methods, the extent to which these actors shared beliefs and assumptions about the fit female body is striking. The paper also makes it clear that it is necessary to move away from national or imperial lenses that have hitherto occluded the global interconnections and border-crossing trajectories at play when analyzing discourses and practices of female physical education in South Asia in the period under purview.